Research on a Review of Derivative Methods of Classical Hydrothermal/Solvothermal Synthesis Methods, Taking SnO₂/r-GO Gas-sensitive Composite Materials as Examples - Tang, Zhuoran (International Journal of Electric Power and Energy Studies, 2025)
Against the backdrop of accelerating global industrialization, the significance of gas sensors in environmental pollution monitoring, energy security, and medical diagnostics has become increasingly prominent. Metal oxide semiconductors, such as SnO₂, have emerged as core materials due to their low cost and high sensitivity, yet they face limitations such as insufficient room-temperature sensitivity and humidity interference. The introduction of two-dimensional materials like graphene offers novel approaches to enhance gas-sensing performance, improving sensor capabilities through mechanisms such as heterojunction formation and increased adsorption sites. The hydrothermal/solvothermal synthesis method has become a mainstream approach for preparing SnO₂/r-GO composites, owing to its operational simplicity and material uniformity. This paper primarily reviews its derivative methods, including the "separate preparation and subsequent synthesis method" and the "co-preparation method." Research indicates that these methods can significantly enhance the sensor's response value, selectivity, and stability towards target gases.